2017
DOI: 10.1007/s11284-017-1518-4
|View full text |Cite
|
Sign up to set email alerts
|

The soil seed bank of a rehabilitated draw‐down zone and its similarity to standing vegetation in the Three Gorges Reservoir Area

Abstract: The reverse seasonal flooding that resulted from the construction of the Three Gorges Project has induced a drastic degradation of draw-down zone vegetation and the seed bank in the reservoir. The composition and distribution of seed banks and their similarities to standing vegetation were determined through field investigations and germination experiments on the vegetation as well as soil seed bank data collected from three restoration sites in Zigui county, Wanzhou city, and Zhongxian county to uncover the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…The structure of soil seedbank and its relationship with the above-ground vegetation are considered a crucial evidence for the recruitment of plant community after disturbance (Capon and Brock 2006;Bossuyt and Honnay 2008;Zhang et al 2017). The results of the soil seedling emergence experiment showed that most species were annual herbs that can adapt to the flood pattern in agreement with results described by Zhang et al (2017); moreover, annuals were more numerous at the lower elevations with perennials at the higher elevations. The similarity of species composition between soil seedbank and above vegetation in the annual community of the lower part was greater than that for the perennial vegetation in the upper part of the drawdown zone.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…The structure of soil seedbank and its relationship with the above-ground vegetation are considered a crucial evidence for the recruitment of plant community after disturbance (Capon and Brock 2006;Bossuyt and Honnay 2008;Zhang et al 2017). The results of the soil seedling emergence experiment showed that most species were annual herbs that can adapt to the flood pattern in agreement with results described by Zhang et al (2017); moreover, annuals were more numerous at the lower elevations with perennials at the higher elevations. The similarity of species composition between soil seedbank and above vegetation in the annual community of the lower part was greater than that for the perennial vegetation in the upper part of the drawdown zone.…”
Section: Discussionsupporting
confidence: 67%
“…The similarity of species composition between soil seedbank and above vegetation in the annual community of the lower part was greater than that for the perennial vegetation in the upper part of the drawdown zone. It is well known that the soil seedbank of annuals certainly plays a more important role in the regeneration of the plant community in frequently disturbed areas (Landman et al 2007;Zhang et al 2017). The composition of the seedbanks was separated along the vertical gradient of the drawdown zone, and hence may play an important role in vegetation regeneration after flood/exposure disturbance in the lower drawdown zone (Zhang et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…These changes were observed during the primary reservoir impoundment and further progressed after six cycles of water‐level fluctuation (Lu, Li, Huang, et al, ; Lu, Li, Jiang, et al, ). The degradation of soil seed banks induced the degradation of standing vegetation, which further affected soil seed banks (Zhang et al, ; Zhang, Chen, Wu, et al, ). It is thus possible that the plant community and soil seed bank will continue to change and reach an equilibrium that meets the changing hydrological conditions of the dam.…”
Section: Discussionmentioning
confidence: 99%
“…In this paper, the Shannon-Wiener diversity index (SWI) ( Zou et al., 2021 ), Patrick richness index (PRI) ( Courkamp et al., 2022 ), Jaccard similarity index (JCI) ( Zhang et al., 2017 ), and Total seed density (TSD) were used to reflect the diversity of seed banks.…”
Section: Methodsmentioning
confidence: 99%